AgRP/NPY Neuron Excitability Is Modulated by Metabotropic Glutamate Receptor 1 During Fasting - Laing, Brenton T.; Li, Peixin; Schmidt, Cameron A.; Bunner, Wyatt; Yuan, Yuan; Landry, Taylor; Prete, Amber; McClung, Joseph M.; Huang, Hu (Frontiers in Cellular Neuroscience, 2018)
The potential to control feeding behavior via hypothalamic AgRP/NPY neurons has led to many approaches to modulate their excitability – particularly by glutamatergic input. In the present study using NPY-hrGFP reporter mice, we visualize AgRP/NPY neuronal metabotropic glutamate receptor 1 (mGluR1) expression and test the effect of fasting on mGluR1 function. Using the pharmacological agonist dihydroxyphenylglycine (DHPG) we demonstrate the enhanced capacity of mGluR1 to drive firing of AgRP/NPY neurons after overnight fasting, while antagonist 3-MATIDA reduces firing. Further, under synaptic blockade we demonstrate that DHPG acts directly on AgRP/NPY neurons to create a slow inward current. Using an in vitro approach, we show that emulation of intracellular signals associated with fasting by forskolin enhances DHPG induced phosphorylation of Extracellularly Regulated-Signal Kinase (1/2) in GT1-7 cell culture. We show in vivo that blocking metabotropic glutamate receptor 1 by antagonist 3-MATIDA lowers fasting induced refeeding. In summary, this study identifies a novel layer of regulation on AgRP/NPY neurons integrated with whole body energy balance.